2022
DOI: 10.1139/cjce-2020-0307
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on sulfate erosion resistance of nano-CaCO3 modified concrete

Abstract: In the saline soil environment of western China, the salts can corrode the ordinary cement concrete seriously, and the durability of concrete structure deteriorates gradually until it fails. This impedes the application of ordinary Portland cement concrete in this area. Aiming at the problem of the short service life of concrete in the harsh environment of western China, this study probes the performance of nano-CaCO<sub>3</sub> modified concrete in a sulfate environment. The durability of the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…It can be seen that the sudden failure of RAC interface transition weakness can not be ignored in fatigue load, and incorporation of NC can effectively improve the N of RAC to a certain extent. As reported by Poudyal et al (2021) and Qiao et al (2022), this may be attributed to the nucleation and microcrack filling effects of NC. The effect of NC can compensate for some deficiencies in the microstructure level of RAC to improve the overall macroscopic structure, and thereby enhance the fatigue resistance of RAC.…”
Section: Fatigue Lifesupporting
confidence: 60%
See 2 more Smart Citations
“…It can be seen that the sudden failure of RAC interface transition weakness can not be ignored in fatigue load, and incorporation of NC can effectively improve the N of RAC to a certain extent. As reported by Poudyal et al (2021) and Qiao et al (2022), this may be attributed to the nucleation and microcrack filling effects of NC. The effect of NC can compensate for some deficiencies in the microstructure level of RAC to improve the overall macroscopic structure, and thereby enhance the fatigue resistance of RAC.…”
Section: Fatigue Lifesupporting
confidence: 60%
“…According to the recommended value of recycled coarse aggregate replacement rate of high-rise buildings in Chinese Standard GB/T 25177-2010, the RCA replacement rates in RAC and NC-RAC are determined to be 30% and 50% by weight. It has been reported that the strength of concrete decreases significantly when the content of NC is higher than 2% (Poudyal et al 2021;Qiao et al 2022). In the experiment, the content of NC was set to 1% and 2% by weight.…”
Section: Materials and Mixture Proportionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this is the same as the adverse effect of the above hydration reaction on the power generation performance of piezoelectric transducers. As the strength of concrete increases, the internal stress continues to increase, and the deformation of the piezoelectric transducer is more restricted, hindering its power generation performance 23 . Finally, when the generated expansion stress exceeds the tensile strength of the concrete, defects begin to appear at the interface between the piezoelectric transducer and the cement paste, which is beneficial to the power generation performance.…”
Section: Piezoelectric‐road Specimens Test Principles In Erosive Envi...mentioning
confidence: 99%
“…As the strength of concrete increases, the internal stress continues to increase, and the deformation of the piezoelectric transducer is more restricted, hindering its power generation performance. 23 Finally, when the generated expansion stress exceeds the tensile strength of the concrete, defects begin to appear at the interface between the piezoelectric transducer and the cement paste, which is beneficial to the power generation performance. Among erosive products, ettringite is the primary cause of destruction.…”
Section: Sulphate Erosionmentioning
confidence: 99%